Lycopene improves the metformin effects on glycemic control and decreases biomarkers of glycoxidative stress in diabetic rats - Figueiredo, Ingrid Delbone [UNESP] (2020)
Introduction: Oxidative stress and exacerbated generation of advanced glycation end products (AGEs) participate in the onset of diabetic complications. Lycopene is a potent antioxidant; evidence accounts for its ability to mitigate diabetic disturbances, including the deleterious events of advanced glycation. Therefore, this carotenoid has emerged as a candidate to be used in combination with antidiabetic drugs, such as metformin, attempting to counteract the glycoxidative stress. This study investigated the effects of the treatments with lycopene or metformin, alone or in combination, on glycoxidative stress biomarkers and antioxidant defenses in diabetic rats. Methods: Streptozotocin-induced diabetic rats were treated for 35 days with lycopene (45 mg/kg) or metformin (250 mg/kg), alone or as mixtures in yoghurt. Plasma levels of glucose, triglycerides, cholesterol, thiobarbituric acid reactive substances and protein carbonyl groups (biomarkers of oxidative damage), fluorescent AGEs (biomarkers of advanced glycation), and paraoxonase 1 activity (antioxidant enzyme) were assessed. Changes in the hepatic and renal levels of glycoxidative damage biomarkers and the activities of antioxidant enzymes were investigated. Results: The combination of lycopene with metformin maintained the beneficial effects of the isolated treatments, improving the glucose tolerance and lipid profile, lessening biomarkers of oxidative damage, and increasing the paraoxonase 1 activity. Besides, the combined therapy caused further decreases in postprandial glycemia, plasma levels of cholesterol and AGEs, avoided lipid peroxidation (plasma, kidney), and increased antioxidant defenses, mainly the activity of superoxide dismutase (liver, kidney), indicating the maintenance of the lycopene effects. Conclusion: Lycopene combined with metformin may act synergistically in the control of postprandial glycemia, dyslipidemia and glycoxidative stress, as well as increased antioxidant defenses, arising as a promising therapeutic strategy to mitigate diabetic complications.